Eosin Y photoredox catalyzed net redox neutral reaction for regiospecific annulation to 3-sulfonylindoles via anion oxidation of sodium sulfinate salts - Rohokale, Rajendra S.; Tambe, Shrikant D.; Kshirsagar, Umesh A. (Organic & Biomolecular Chemistry, 2018)
An eosin Y photoredox catalyzed net redox neutral process for 3-sulfonylindoles via the anionic oxidation of sodium sulfinate salts and its radical cascade cyclization with 2-alkynyl-azidoarenes was developed with visible light as a mediator. The reaction offers metal and oxidant/reductant free, visible light mediated vicinal sulfonamination of alkynes to 2-aryl/alkyl-3-sulfonylindoles and proceeds via the generation of a sulfur-centered radical through direct oxidation of the sulfinate anion by an excited photocatalyst with a reductive quenching cycle. The mild conditions, use of an organic dye as photo-catalyst, bench stability and easily accessible starting materials make the present approach green and attractive.

Metal-free synthesis of 3-thiocyanatobenzothiophenes by eosin Y photoredox-catalyzed cascade radical annulation of 2-alkynylthioanisoles - Tambe, Shrikant D.; Jadhav, Mahesh S.; Rohokale, Rajendra S.; Kshirsagar, Umesh A. (European Journal of Organic Chemistry, 2018)
A convenient, efficient, metal-free synthesis of 3-thiocyanatobenzothiophenes has been developed that uses eosin Y in a visible-light-mediated photoredox-catalyzed anion oxidation of the ammonium salt of thiocyanate and proceeds through the cascade radical annulation of 2-alkynylthioanisole at room temperature. The present protocol requires visible light as a green energy source, an organic dye as the photocatalyst, and oxygen as a green oxidant to provide a mild route with a broad substrate scope for the formation of potentially bioactive 3-substituted benzothiophene derivatives in good yields.

Visible-light-mediated eosin Y photoredox-catalyzed vicinal thioamination of alkynes: radical cascade annulation strategy for 2-substituted-3-sulfenylindoles - Tambe, Shrikant D.; Rohokale, Rajendra S.; Kshirsagar, Umesh A. (European Journal of Organic Chemistry, 2018)
An organic dye photoredox-catalyzed regiospecific radical cascade annulation strategy of 2-alkynyl-azidoarenes to generate 3-sulfenylindoles via vicinal thioamination of alkynes at room temperature, mediated by visible light, was developed. The method requires mild conditions, including visible light as a traceless green energy source, room temperature, eosin Y organic dye as a photoredox catalyst, ambient air as oxidant, and easily available starting materials to provide a green, efficient, metal- and strong-oxidant-free synthesis of 3-sulfenylindoles with broad substrate scope through vicinal thioamination of alkynes.

Iridium(III)-catalyzed alkynylation of 2-(Hetero)arylquinazolin-4-one scaffolds via C-H bond activation - Rohokale, Rajendra S.; Kalshetti, Rupali G.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2019)
The directed C-H alkynylation of 2-(hetero)arylquinazolin-4-ones has been explored with the ethynylbenziodoxolone reagent TIPS-EBX employing an Ir(III) catalyst. Complementary conditions for either monoalkynylation or dialkynylation have been developed. Also demonstrated is the broad scope of this reaction and the compatibility of various functional groups such as -F, -Cl, -Br, -CF3, -OMe, -NO2, and alkyl, etc.